Reliability of a novel printed piezoresistive pressure sensor - Burnie, L.; Holder, A.; Claypole, T.; Kilduff, L.; Bezodis, N. (ISBS Proceedings Archive (Michigan), 2020)
Printed pressure sensors have the potential to be useful for measuring pressure in a multitude of sports biomechanics applications. This study was a proof of concept of a novel printed piezoresistive pressure sensor array with the aim of assessing the reliability of the sensor. The relationship between the force applied to the sensor and resistance was well described by an exponential equation (r2 > 0.962), which provides confidence in the piezoresistive nature of the response. This demonstrates that, with further refinement and development, the currently-designed pressure sensor array has the potential to measure pressure during field-based sporting movements. Further research and development are required to improve reliability and to test sensor performance under dynamic loading conditions similar to those typically experienced in sport.